BUDAYA TOLERAN: SETTING SOSIAL ‘SEMARANGAN’ - Abdul Kholiq (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2018)
The study of harmonious and tolerant culture is still an actual topic, in the midst of thenation’s condition facing an era of strengthening of the transnational movement that threatensnational integration. As a pluralist nation, on the one hand it is a potential for national identity,on the other hand it can potentially cause conflict based on SARA. This paper describes theharmonious and tolerant culture built by Semarangan residents. A harmonious and tolerantculture in the social life of Semarangan residents comes from the consciousness or the mind ofthe Javanese people who consider religion not as social ‘isme’, but rather understood as somethingprivate. For Javanese, religion is ‘ageman’ or clothing that may be different or changed. Themeaning of ‘religion’ lies in how the person believes and practices it. Religious people are judgednot from what religion they embrace, but how much can give meaning to their society.Keywords: Culture, Harmonious, Tolerant, Religion